2019
DOI: 10.1002/pchj.316
|View full text |Cite
|
Sign up to set email alerts
|

Effort–cost computation in a transdiagnostic psychiatric sample: Differences among patients with schizophrenia, bipolar disorder, and major depressive disorder

Abstract: Amotivational symptoms are observed in schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD).Effort-cost computation may be a potential contributor to amotivation transdiagnostically. This study examined effort-cost computation in these three diagnostic groups. This study recruited 141 outpatients (49 SCZ, 52 non-psychotic BD, and 40 non-psychotic MDD) and 57 healthy controls (HCs). We administered the Effort-Expenditure for Reward Task (EEfRT), which manipulated different levels of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 62 publications
8
33
3
Order By: Relevance
“…Reward wanting in healthy people is an ability to balance costs and benefits when selecting from multiple options (Treadway et al, 2009). However, it has been reported that patients with major depressive disorder (MDD), bipolar disorder (BD) and schizophrenia display reduced effort to gain reward and fail to respond optimally to uncertain rewards (Barch et al, 2014;Treadway et al, 2012;Wang et al, 2015;Yang et al, 2014;Zou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Reward wanting in healthy people is an ability to balance costs and benefits when selecting from multiple options (Treadway et al, 2009). However, it has been reported that patients with major depressive disorder (MDD), bipolar disorder (BD) and schizophrenia display reduced effort to gain reward and fail to respond optimally to uncertain rewards (Barch et al, 2014;Treadway et al, 2012;Wang et al, 2015;Yang et al, 2014;Zou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…impaired anticipatory pleasure and consummatory pleasure in MDD [32], but bias toward impairment in anticipatory pleasure in schizophrenia [20,[29][30][31]). Furthermore, recent studies employing reward task-choice behavioral analyses have suggested that there may be distinct clinically important motivation impairments in relation to anhedonia in patients with schizophrenia, bipolar disorder, and MDD [65,66]. Hence, measurement invariance provides confidence that TEPS score differences reflect authentic differences across the wellestablishedanticipatory-consummatory pleasure dimension as well as across a newly exposed motivationnonmotivation dimension in future research.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies using such "value-based choice" tasks have found that, compared to healthy controls, people with depression and schizophrenia are less willing to expend greater effort for larger or more probable rewards. While in some studies depressed participants expended less effort overall (Treadway et al 2012;Hershenberg et al 2016), in most studies participants with depression (Cléry-Melin et al, 2011;Yang et al, 2014;Zou et al, 2020) and schizophrenia (Barch et al, 2014;Chang et al, 2019;Fervaha et al, 2013;Gold et al, 2013;McCarthy et al, 2016;Treadway et al, 2015;Yang et al, 2021;Zou et al, 2020) did not differ from healthy controls in their overall willingness to expend effort; instead, anhedonic individuals were less willing to expend greater effort when the magnitude or probability of reward were high. Although some studies in depression (Yang et al, 2021) and schizophrenia (Docx et al 2015) reported divergent results, overall the pattern is remarkably consistent (although this may be due in part to publication bias; Halahakoon et al, 2020).…”
Section: Behavioural Studiesmentioning
confidence: 89%